Product design modeling using CAD/CAE : the computer aided engineering design series - Chang, Kuang-Hua, 1960- (Computer aided engineering design series., 2014)
"Product Design Modeling using CAD/CAE is the third part of a four-part series. It is the first book to integrate discussion of computer design tools throughout the design process. Through this book, you will: Understand basic design principles and all digital design paradigms Understand computer-aided design, engineering, and manufacturing (CAD/CAE/CAM) tools available for various design-related tasks Understand how to put an integrated system together to conduct all-digital design (ADD) Provides a comprehensive and thorough coverage of essential elements for product modeling using the virtual engineering paradigm Covers CAD/CAE in product design, including solid modeling, mechanical assembly, parameterization, product data management, and data exchange in CAD Case studies and tutorial examples at the end of each chapter provide hands-on practice in implementing off-the-shelf computer design tools Provides two projects showing the use of Pro/ENGINEER and SolidWorks to implement concepts discussed in the book."- Resumé vydavatel